(3ebGeI GdcSfhSis - (3CHh YHO Gddg GdhRjQ eMeO Hf CMeO GcfShS GdbQTj GdShSj GdeQGcTj, GcSfhS,J (B1294 (3g` s
(3ChdgG (B:s
(3MOKfG HTQ Hf aQM Yf fSje Hf CQL bGd cfJ jhe CXdfi s
(3BNQgG (B:s
(3LYdJGg JeGe GdfSc, aLGAJ hNJGegG eSc GfJgJ s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B19s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B96 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B- (3GdQHGW (B(D 1270) s
Keywords: (3GdCOHs